THE EFFECT OF COMPENSATION, JOB STRESS, AND MOTIVATION ON JOB SATISFATION - HERAWAN, ANNISA HERWINA; HARYADI, HARYADI; INDYASTUTI, DEVANI LAKSMI (INDONESIAN RESEARCH SOCIETY, 2019)
This study aims to determine and analyze the effects of compensation, job stress andmotivation on job satisfaction. The method used is survey and sampling technique used isnonprobability sampling with saturated sampling. Population in this research is permanentemployee of Health Office Karawang with sample counted 100 respondent. Data analysisused in this research is using Partial Least Square (PLS). The implication of this research isto improve employee job satisfaction, the management of Karawang Health Office needs toprioritize policies related to job satisfaction. In an effort to improve employee job satisfaction,management needs to prioritize policies related to compensation, job stress and motivation.To improve employee job satisfaction, management also needs to pay attention to othersupporting factors such as organizational culture, work environment, organizational climate,organizational commitment and other factors not examined. It should be noted in order toimprove employee morale and progress of the company